Metabolomic Analysis of Lactobacillus acidophilus, L. gasseri, L. crispatus, and Lacticaseibacillus rhamnosus Strains in the Presence of Pomegranate Extract - Chamberlain, MaryClaire; O'Flaherty, Sarah; Cobián, Natalia; Barrangou, Rodolphe (Frontiers in Microbiology, 2022)
Lactobacillus species are prominent inhabitants of the human gastrointestinal tract that contribute to maintaining a balanced microbial environment that positively influences host health. These bacterial populations can be altered through the use of probiotic supplements or via dietary changes which in turn affect host health. Utilizing polyphenolic compounds to selectively stimulate the growth of commensal bacteria can have a positive effect on the host through the production of numerous metabolites that are biologically active. Four Lactobacillus strains were grown in the presence of pomegranate extract (POM). Two strains are commonly used probiotics; L. acidophilus NCFM and L. rhamnosus GG, while two exhibit probiotic potential; L. crispatus NCK1351 and L. gasseri NCK1342. To compare and contrast the impact of POM on the strains’ metabolic capacity, we investigated the growth of the strains with and without the presence of POM, as well as identified their carbohydrate utilization and enzyme activity profiles. To further investigate the differences between strains, an untargeted metabolomic approach was utilized to quantitatively and qualitatively define the metabolite profiles of these strains. Several metabolites were produced significantly and/or exclusively in some of the strains, including mevalonate, glutamine, 5-aminoimidazole-4-carboxamide, phenyllactate, and fumarate. The production of numerous discrete compounds illustrates the unique characteristics of and diversity between strains. Unraveling these differences is essential to understand probiotic function and help inform strain selection for commercial product formulation.